A clinical history of Zincum metallicum: homeopathic pathogenetic trials and case reports. Issue 2 (May 2017) - Waisse, Silvia; Jurj, Gheorghe
Abstract : In the present study, we investigated the experimental basis for the indications of homeopathic drug Zincum metallicum . The current body of knowledge about Zinc met has a core composed of pathogenetic and clinical data collected in the 19th century surrounded by layers of clinical observations reported over time. In the description, we prioritized poorly known sources, especially the ones that were never translated from the original German. We also performed quantitative and statistical analysis of repertory data. Through a literature survey and a call to practicing homeopathic doctors from many countries, we were able to put together a relevant case-series that represents homeopathic indications of Zinc.